Carry the rock race, football, and the soul of an American city - Jennings, Jay (The University of Arkansas Press, 2023)
"In 2007, as the fiftieth anniversary of the fight to integrate Little Rock Central High School approached, veteran sportswriter and native son of Little Rock Jay Jennings returned to his hometown to take the pulse of the city and the school. He found a compelling story in Central High's football team, where Black and white students toiled under longtime coach Bernie Cox, whose philosophy of discipline and responsibility and punishing brand of physical football had led the team to win seven state championships. Carry the Rock tells the story of the dramatic ups and downs of a high school football season and reveals a city struggling with its legacy of racial discrimination and the complex issues of contemporary segregation"--
Originally published: Emmaus, Pa. : Rodale, 2010
Not distributed; available at Arkansas State Library
Keywords: Central High School (Little Rock, Ark.) / Football; Football / Arkansas / Little Rock; Central High School (Little Rock, Ark.) / History; Little Rock (Ark.) / Race relations / History; Central High School (Little Rock, Ark.); Football; Race relations; Arkansas / Little Rock; History